The parasites of my rival are my friends - Orlansky, Sigal; Ben-Ami, Frida (Frontiers in Microbiology, 2023)
The competitive exclusion principle asserts that two species cannot stably coexist in the same habitat. However, the presence of a parasite can facilitate temporary coexistence between two host species occupying the same habitat. Studies of parasite-mediated interspecific competition typically use two host species that are both susceptible to a single parasite species, as it is rare to find a resistant host species that requires a parasite to enable coexistence with a competitively superior susceptible host. We therefore investigated how two host species characterized by different susceptibility profiles affect each other when they coexist in the same habitat, by conducting two long-term mesocosm experiments in the laboratory. We followed populations of D. similis coexisting with D. magna, in either the presence or absence of the microsporidium Hamiltosporidium tvaerminnensis and then the bacterium Pasteuria ramosa. We found that in the absence of parasites, D. magna competitively excluded D. similis within a short period of time. However, in the presence of either parasites, the competitive ability of D. magna decreased dramatically. Our results emphasize the importance of parasites in shaping community structure and composition, by allowing coexistence of a resistant host species that would otherwise become extinct.